Designing a Voice User Interface for Accessible Campus Mobility Services at Telkom University: A Double Diamond Approach - Muhamad Roihan AlAzhari; Didit Widiatmoko Soewardikoen; Dandi Yunidar; Apdanil Syukri; Saftika Wulandari (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
This study aims to design and evaluate a technology-based campus transportation service to improve accessibility and information delivery at Telkom University. The research employs a design-based research approach using the Double Diamond model, with data collected through observations, interviews, questionnaires, and literature review. The design process resulted in a service prototype that was evaluated using the User Experience Questionnaire (UEQ). The evaluation results show positive scores across all UEQ dimensions, including attractiveness, clarity, efficiency, stimulation, and novelty. These findings indicate that the proposed service provides a good user experience and supports the development of an innovative and sustainable campus transportation system.